DIGITAL TRANSFORMATION IN SCIENCE EDUCATION - Sabariah, Hayatun; Fuadi, Ahmad; Syahfitri, Diani; Ridha, Zaifatur; Misdaramayani, Nur (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
Actually, the use of digital transformation in science education is not a new thing in education. This has been around for the past five to 4 years. However, education in Indonesia has only just become lively in using it because there was a proposal from the education minister who proclaimed to use digital transformation in the world of education. And even more lively in its use when the Covid-19 virus attacks the territory of the State of Indonesia. The policy of the minister of education in teaching and learning activities using distance learning. Either you can use the Zoom meeting application, Google Meeting, Google Classroom and so on. This is expected to increase teaching and learning activities throughout Indonesia such as activities carried out face-to-face. This is the new face of the world of education in Indonesia, all moving towards digital technology. The demands of the times that continue to move in accessing various information are likewise, inseparable from the advancement of digital technology. Dragging educators in using technology must also be able to. Both in use as a learning medium or a strategy in teaching and learning activities.